Model Endapan Nikel Laterit Daerah Molawe Kabupaten Konawe Utara Provinsi Sulawesi Tenggara - Raivel, Raivel; Hasrianto, Hasrianto (Mining Science And Technology Journal, 2023)
Southeast Sulawesi is an area that has the number one largest laterite nickel reserves in Indonesia and there are industrial companies in laterite nickel processing. This study aims to determine the nickel laterite model as a reference in exploration and mining. The research method used was field observation through drilling data and modeling of nickel deposits with surpac 6.5.1 software, while laboratory analysis used XRF (X-Ray Fluorescence). The results showed that the limonite, saprolite and badrock layers had different thicknesses and Ni levels for each layer and drill point. The limonite layer has a thickness of 3 -10 meters with a Ni content of 0.29 - 1.38% and Fe 19 - 53%, saprolite has a thickness of 2 - 13 with a Ni content of 1.40 - 2.34% and Fe 5.79 - 40 ,44 %. Based on the nickel deposit block model, the total volume and tonnage at COG Ni 1.4% is 98,573 M3 and 128,145 WMT with a total Ni content of 1.61%, the total volume and tonnage at COG Ni 1.6% is 51,342 M3 and 66,745 WMT with a total Ni content is 1.71%, total volume and tonnage at COG Ni 1.6% is 51,342 M3 and 66,745 WMT with a total Ni content of 1.71%.